Cardiac mechanisms of the beneficial effects of SGLT2 inhibitors in heart failure: Evidence for potential off-target effects. (June 2022) - Dyck, Jason R.B.; Sossalla, Samuel; Hamdani, Nazha; Coronel, Ruben; Weber, Nina C.; Light, Peter E.; Zuurbier, Coert J.
Abstract: Sodium glucose cotransporter 2 inhibitors (SGLT2i) constitute a promising drug treatment for heart failure patients with either preserved or reduced ejection fraction. Whereas SGLT2i were originally developed to target SGLT2 in the kidney to facilitate glucosuria in diabetic patients, it is becoming increasingly clear that these drugs also have important effects outside of the kidney. In this review we summarize the literature on cardiac effects of SGLT2i, focussing on pro-inflammatory and oxidative stress processes, ion transport mechanisms controlling sodium and calcium homeostasis and metabolic/mitochondrial pathways. These mechanisms are particularly important as disturbances in these pathways result in endothelial dysfunction, diastolic dysfunction, cardiac stiffness, and cardiac arrhythmias that together contribute to heart failure. We review the findings that support the concept that SGLT2i directly and beneficially interfere with inflammation, oxidative stress, ionic homeostasis, and metabolism within the cardiac cell. However, given the very low levels of SGLT2 in cardiac cells, the evidence suggests that SGLT2-independent effects of this class of drugs likely occurs via off-target effects in the myocardium. Thus, while there is still much to be understood about the various factors which determine how SGLT2i affect cardiac cells, much of the research clearly demonstrates that direct cardiac effects of these SGLT2i exist, albeit mediated via SGLT2-independent pathways, and these pathways may play a role in explaining the beneficial effects of SGLT2 inhibitors in heart failure. Graphical abstract: Graphical summary: Pathophysiology involved in HFpEF and the potential mechanisms of how SGLT2i may improve HFpEF. As comorbidities play a major role in HFpEF, the positive influence of SGLT2i on hypertension, diabetes, obesity, and hypertension is of importance. Moreover, SGLT2i can directly influence myocardial pathological processes underlying HfpEF as reported in this review. HFpEF: heart failure with preserved ejection fraction; NO: nitric oxide; SGLT2i: sodium-glucose-cotransporter 2 inhibitors. Unlabelled Image